The need for accurate long‐term measurements of water vapor in the upper troposphere and lower stratosphere with global coverage. Issue 2 (8th February 2016) - Müller, Rolf; Kunz, Anne; Hurst, Dale F.; Rolf, Christian; Krämer, Martina; Riese, Martin
Abstract: Water vapor is the most important greenhouse gas in the atmosphere although changes in carbon dioxide constitute the "control knob" for surface temperatures. While the latter fact is well recognized, resulting in extensive space‐borne and ground‐based measurement programs for carbon dioxide as detailed in the studies by Keeling et al. (1996), Kuze et al. (2009), and Liu et al. (2014), the need for an accurate characterization of the long‐term changes in upper tropospheric and lower stratospheric (UTLS) water vapor has not yet resulted in sufficiently extensive long‐term international measurement programs (although first steps have been taken). Here, we argue for the implementation of a long‐term balloon‐borne measurement program for UTLS water vapor covering the entire globe that will likely have to be sustained for hundreds of years. Key points: Water vapor is the most important greenhouse gas Currently atmospheric water vapor is not measured accurately enough A global, long‐term balloon borne measurement program should be implemented